Adaptasi Instrumen Academic Expectation Stress Inventory-9 (AESI-9) pada Siswa SMA - Andika Novia Putri Rachmawati; Charaka Bintang Nararya; Wisnu Samodra; Femmi Nurmalitasari (Flourishing Journal, 2024)
Research on Academic Expectations Stress Inventory-9 (AESI-9) is important because it has an essential role as a risk factor for stress due to parents' academic expectations for their children. However, the measuring instrument in the Indonesian version has not been found. The purpose of this study was to adapt the Academic Expectations Stress Inventory-9 (AESI-9) instrument into the Indonesian version. This study was conducted online using a Google Form link intended for high school students in Indonesia (N=40; 21 male subjects and 19 female subjects) aged 16-19 years. The results of the validity test showed that all AESI-9 adaptation instruments were appropriate because they had an Aiken's V assessment >0.6. The results of the reliability test based on the Cronbach's Alpha value were 0.871. This instrument can be considered reliable and categorized as strong because the value exceeds 0.6 which is the reliability standard. The discriminatory power of the instruments in this study met the standard, which was above 0.3. The statistical results show that the high category has a value of 14, the medium category has a value of 12, the low category has a value of 11, and the very low category has a value of 3. AbstrakPenelitian mengenai Academic Expectations Stress Inventory-9 (AESI-9) ini penting karena memiliki peran yang esensial sebagai faktor risiko stres akibat ekspektasi akademik orang tua terhadap anaknya. Akan tetapi, alat ukur dalam versi Bahasa Indonesia masih belum ditemukan. Tujuan penelitian ini untuk mengadaptasi instrumen Academic Expectations Stress Inventory-9 (AESI-9) ke dalam versi Bahasa Indonesia. Penelitian ini dilakukan secara online menggunakan link Google Form yang ditujukan untuk siswa dan siswi Sekolah Menengah Atas (SMA) di Indonesia (N=40; 21 subjek laki-laki dan 19 subjek perempuan) yang berusia antara 16-19 tahun. Hasil uji validitas menunjukkan bahwa seluruh instrumen adaptasi AESI-9 sesuai karena memiliki penilaian Aiken’s V >0,6. Hasil uji reliabilitas yang didasarkan dari nilai Cronbach’s Alpha sebesar 0,871. Instrumen ini dapat dianggap reliabel dan dikategorikan kuat karena nilai tersebut melebihi 0,6 yang merupakan standar reliabilitas. Daya beda instrumen pada penelitian ini memenuhi standar yaitu di atas 0,3. Hasil statistik menunjukkan bahwa kategori tinggi memiliki nilai 14, kategori sedang bernilai 12, kategori rendah bernilai 11, dan kategori sangat rendah senilai 3.